2012
DOI: 10.5114/ceji.2012.30803
|View full text |Cite
|
Sign up to set email alerts
|

Clinical immunology Density of Langerhans cells in chronic plaque psoriatic lesions before and after phototherapy

Abstract: Introduction: Langerhans cells (LCs) constitute a key component of the skin immune system (SIS Novocastra). Results: The number of LCs in the study group was lower in lesional skin compared to perilesional skin. After phototherapy we observed an increase in the number of LCs in lesional skin while a decrease of the LCs number was noted in perilesional skin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
2
4
0
1
Order By: Relevance
“…This is further complicated by conflicting results and whether treatment affects the number of LCs in psoriatic skin. 28,[54][55][56][57][58] However, in agreement with a study on the effect of sun on macrophages and dendritic cells, we found a reduction in both cell types. 33 The number of LCs was significantly increased in LS compared with NL skin at baseline.…”
Section: Discussionsupporting
confidence: 92%
“…This is further complicated by conflicting results and whether treatment affects the number of LCs in psoriatic skin. 28,[54][55][56][57][58] However, in agreement with a study on the effect of sun on macrophages and dendritic cells, we found a reduction in both cell types. 33 The number of LCs was significantly increased in LS compared with NL skin at baseline.…”
Section: Discussionsupporting
confidence: 92%
“…The level of LC has previously been reported to be downregulated in lesional psoriatic skin, but discrepancies in the reported results exist . These discrepancies could be due to the use of different quantification methods.…”
Section: Discussionmentioning
confidence: 84%
“…The role of LC in the pathogenesis of psoriasis remains unknown. It has been shown that the number of LC is downregulated in lesional psoriatic skin, but conflicting results exist . Moreover, the depletion of LC in psoriasis aggravated psoriasis symptoms during ongoing disease in a mouse model where psoriasis‐like skin diseases were mimicked by deletion of Jun and JunB genes via a tamoxifen‐inducible cre recombinase in keratin‐5‐expressing cells .…”
Section: Introductionmentioning
confidence: 99%
“…Its determination is also used in non-neoplastic lesions which are characterized by uncontrollable proliferation of cells, for example in psoriasis [10]. In this disease, excessive proliferation of cells and an improper keratinization process, together with immune disorders, belong to basic pathogenetic mechanisms [11,12]. Epidermal hyperproliferation is connected with intense cell proliferation in the basal layer and too rapid, thus irregular keratinocyte maturation.…”
Section: Introductionmentioning
confidence: 99%